Indonesian Experiences in Retrofitting of Some Milk Cooler Systems - Pasek, Ari D.; Tandian, N. P; Suwono, A; Hardianto, T; Soelaiman, T. A Fauzi (Mesin, 1999)
To overcome the ozone layer depletion problem, the Indonesian government has ratified the Montreal protocol and its amendments. The import of R-12 refrigerant to Indonesia has been banned since the end of 1997. Meanwhile, most of Indonesian milk cooling units use R-12. Therefore, it is expected that these cooling units have to be switched to other refrigerant soon. Almost all of Indonesian milk cooling units belong to small or medium dairy cooperatives that cannot aï¬ord to retroï¬t their systems to R-134a. In this research, a milk-cooling unit designed for R-12 was directly switched to propane/butane refrigerants (propane-isobutane, and propane/n-butane refrigerants) without any modiï¬cation. The performances of the milk-cooling unit operated with propane/isobutane, propane/n-butane and R-12 geï¬igerants were investigated. It was found that propane/n~bntane reï¬igerant is the most eï¬icient, and followed by propane/isobutane and R-12. Results of several other milk cooling units were also reported.